PENGARUH EKSTRAKURIKULER ROHANI ISLAM (ROHIS) TERHADAP SIKAP SPIRITUAL SISWA (Survey di SMK Negeri 46 Jakarta) - Rohimah, Rohimah (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research aims to determine the influence of Islamic spiritual extracurriculars (rohis) on spiritual attitudes. This research was carried out on students at SMK Negeri 46 Jakarta from June to August 2021. This research method was descriptive with a quantitative approach, and the analysis used simple linear regression analysis. The sampling technique in this research is using a saturated sample where the sample is a population, namely 30 respondents who are active members of the Islamic spiritual extracurricular classes 11 and 12. The research instrument used is a questionnaire using a Likert scale on variables X and Y. Research results show that Islamic spiritual extracurriculars (rohis) have a significant influence on spiritual attitudes. This is shown by the results of the regression test using the t test; the t count is 2.121 and the t table at the 5% significance level is 2.0448, and because t count > t table, the conclusion is that Islamic spiritual extracurriculars have a significant influence on students' spiritual attitudes